(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Iron deficiency is the most important but preventable nutritional problem in Bangladesh. Thyroid peroxidase, an iron containing enzyme, is essential for initial two steps of thyroid hormone synthesis which is a component of tissue iron. Tissue iron diminishes early in the course of iron deficiency. So thyroid hormone level may be altered in iron deficient patients. This case-control study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2006 to June 2007. This study was done to find out the changes of thyroid hormonal activity in iron deficiency. In this study 72 subjects were selected from the out-patient department of the hospital. Patients with low serum ferritin level <12 mgm/L were selected as cases (n=36) and healthy persons with normal serum ferritin level were taken as controls. Serum ferritin, thyroid stimulating hormone (TSH), free thyroxine (FT4) and free triiodothyronine (FT3) were measured in all study subjects. Values were expressed as mean ± SD. Unpaired ’t’ test and Pearson’s correlation test were performed to see the level of significance and p value <0.05 was taken as significant. Serum ferritin level in cases and controls were 6.78±4.05 mgm/L and 79.04±28.08 mgm/L respectively which showed significant difference (P<0.0001). Serum TSH concentration in cases and controls were 3.32±1.54 mIU/L and 1.89±0.86 mIU/L respectively. Serum FT4 concentration in cases and controls were 11.66±1.77 pmol/L and 13/10±1.36 pmol/L respectively and that of FT3 were 3.00±0.68 and 3.31±0.61 pmol/L respectively. All showed significant difference between groups. Serum ferritin and Serum TSH showed significant negative correlation in controls whereas in cases they showed negative correlation which was not statistically significant. Both serum FT4 and FT3 revealed positive correlation with serum ferritin but that too was not significant statistically. Though the study failed to show any significant positive correlation between serum ferritin and thyroid hormones, lower level of thyroid status in iron deficient patients suggest that it could be a reflection of disturbed activities of iron dependent enzymes such as thyroid peroxidase that impairs thyroid hormone synthesis. However, a large scale study is recommeded to establish the fact. This study showed that there was significant difference in thyroid hormonal status between iron deficient patients and normal healthy persons. Therefore it can be concluded that iron deficiency may impair normal thyroid hormone status. DOI: http://dx.doi.org/10.3329/bjmb.v5i1.13424 Bangladesh J Med Biochem 2012; 5(1): 5-11